Maintenance of nutrients’ concentration in sorghum (Sorghum bicolor L.) using brackish water through leaching fraction strategy - Manzoor , Muhammad Zeeshan; Sarwar, Ghulam; Zafar, Ayesha; Mujeeb, , Fakhar; Khadija, Faheem (Journal of Pure and Applied Agriculture, 2023)
Brackish ground water is a major factor of secondary salinity in Pakistan and practice of leaching fraction (LF) may help to keep the salt contents within the desired levels in the root zone. In this study, three types of water (canal water, water with EC = 2 dSm-1 and water with EC = 3 dSm-1 ) was used as such and with leaching fraction of 10 and 20 %. Randomized complete block design (RCBD) was applied to make layout of the experiment. The experiment comprised of 9 treatments replicated four times; T1 = EC 0.23 dS m-1 (canal water), T2 = EC 2.0 water, T3 = EC 3.0 water, T4 = T1 + 10 % LF, T5 = T2 + 10 % LF, T6 = T3 + 10 % LF, T7 = T1 + 20 % LF, T8 = T2 + 20 % LF and T9 = T3 + 20 % LF. Sorghum was used as a test crop. Sorghum plants samples were collected from all plots for laboratory analysis. The maximum nitrogen, phosphorous, potassium, calcium and magnesium contents were noted in the sorghum plants that were harvested from the plots having T1 + 20 % LF (T7). However, the minimum nitrogen, phosphorous and magnesium contents were observed in the plots of treatment T3 getting water with EC 3.0 dSm-1 . However, T3 resulted the highest sodium contents (0.35%) in sorghum plants. In short, technique of leaching fraction proved to be useful to overcome the bad effects of saline water on the concentration/content of various elements present in sorghum plants.